2013
DOI: 10.1016/s0924-9338(13)75722-5
|View full text |Cite
|
Sign up to set email alerts
|

311 – Termination of pregnancy and mental health

Abstract: Abortion may result in traumatized psyche as a complication. Trauma on a woman's thoughts, feelings, dreams, fantasies, intentions, and relations changing her attitude to life as such, to her nearest, also to the values and eventually to herself. The consequences occurring as uncontrolled chain reaction affect her family life, career and communication; they break her as personality and lead towards destruction. There is always a risk of suicide. In psychiatry, termination of pregnancy is very important as it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The free comment section showed that students highly valued abortion clinic placement and recommended increasing such exposure as only 18 out 79 (22.8%) students had such an opportunity. Emerging evidence suggests that sensitive counselling, multidisciplinary team involvement and psychological support are also essential for abortion care; 17–19 however, these were not included in the updated RANZCOG medical school curriculum 8 …”
Section: Discussionmentioning
confidence: 99%
“…The free comment section showed that students highly valued abortion clinic placement and recommended increasing such exposure as only 18 out 79 (22.8%) students had such an opportunity. Emerging evidence suggests that sensitive counselling, multidisciplinary team involvement and psychological support are also essential for abortion care; 17–19 however, these were not included in the updated RANZCOG medical school curriculum 8 …”
Section: Discussionmentioning
confidence: 99%